Tomato Quality during Short-Term Storage Assessed by Colour and Electronic Nose - Valeria Messina; Pía Guadalupe Domínguez; Ana Maria Sancho; Noemi Walsöe de Reca; Fernando Carrari; Gabriela Grigioni (International Journal of Electrochemistry)
An assay based on an electronic olfactory system was set to evaluate tomato fruits by sensing the aromatic volatiles during postharvest storage of 21 days at 19±0.5∘C in darkness. Olfactory system measurements were coupled with colour values. Odour profile and senescence parameters were carried out at 7-day intervals. Discriminant function analysis applied to electronic nose data showed three components, accounting for 99.2% of the total variance. In the present assay, separation among groups according to storage time (0, 7, and 14 days) was observed for wildtype. Overexpressed (Money Maker) lines/plants of tomato showed difference between odour profile for day 0 and day 21, even tough a no clear discrimination between 7 and 14 days was observed. Fruit lost weight almost linearly with shelf life (𝑃<0.001) presenting an averaged loss of 21% (𝑟2=0.98) for over-expressed (Money Maker) lines/plants, 13% (𝑟2=0.97) for silenced (Money Maker), and 14% (𝑟2=0.98) for wild type during 21 days of storage. Colour values 𝐿∗, 𝑎∗, and 𝑏∗ data showed that colour properties changed during storage for all the lines considered. Correlations between odour profiles and colour parameter were obtained showing that the electronic nose is a useful technique for monitoring short-term storage of tomato.